2023
DOI: 10.3390/dj11020028
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Laser Thermal Effect on Histological Evaluation of Oral Soft Tissue Biopsy: Systematic Review

Abstract: The aim of the study is to review the literature to observe studies that evaluate the extent of the thermal effect of different laser wavelengths on the histological evaluation of oral soft tissue biopsies. An electronic search for published studies was performed on the PubMed and Scopus databases between July 2020 and November 2022. After the selection process, all the included studies were subjected to quality assessment and data extraction processes. A total of 28 studies met the eligibility criteria. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…De acordo com a revisão sistemática de literatura de Tenore et al, 2023, a maioria dos trabalhos estudados concluíram que o efeito térmico de diferentes comprimentos de onda do laser não prejudicava o diagnóstico histológico das amostras teciduais. 19 Seu prognóstico se mostra favorável após a remoção da lesão, desde que a causa e a lesão tenham sido removidos por completo, apresentando então baixa frequência de recidivas. 14…”
Section: Discussionunclassified
“…De acordo com a revisão sistemática de literatura de Tenore et al, 2023, a maioria dos trabalhos estudados concluíram que o efeito térmico de diferentes comprimentos de onda do laser não prejudicava o diagnóstico histológico das amostras teciduais. 19 Seu prognóstico se mostra favorável após a remoção da lesão, desde que a causa e a lesão tenham sido removidos por completo, apresentando então baixa frequência de recidivas. 14…”
Section: Discussionunclassified
“…Thus, the power density increased and more thermal changes came from the same optical fiber in the same area of tissue as Tenore et al reported in their diode laser review of thermal damage. 12,13,[15][16][17][18] Pigments (melanin, hemoglobin, and protein) are the main chromophores in the range of diode lasers (808-1064 nm). However, water, which makes up more than 70% of most tissues, is not a chromophore and creates almost minimal interaction at diode wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…Diode laser use in dentistry and oral surgery is widely supported by literature, mainly for soft tissue surgery (both for benign and malignant lesions) [41][42][43], providing a fast and not-bleeding lesion removal with (usually) second intention healing of the covering mucosa, as well as the transmucosal or intralesional photocoagulation of vascular malformations (thus avoiding invasive and unpredictable surgical procedures as in the past years) or lesions with high risk of intraoperative bleeding before the surgical removal [44]. It is relevant to underline that the use of diode laser was debated due to the risk of thermal alterations at the histologic examination, but it is fully demonstrated that the thermal effect is usually very low and doesn't affect the histological diagnosis [45]. Therefore, diode laser excision is highly suggestable for patients with reduced compliance, including children, and with similar lesions reported herein [27,31].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%